Overview of Student Perceptions of Traditional Sports at Universitas Negeri Makassar - Arifuddin Usman; Arimbi; Wahyana Wahid; Said Zainuddin (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Traditional sports have cultural values and can play a vital role in improving physical fitness and preserving cultural heritage. The popularity of traditional sports has shifted over time. This study uses a qualitative descriptive approach to determine students' perceptions of traditional sports. The sample of this study involved 217 active students of the Faculty of Sports and Health Sciences at Makassar State University. This study used a questionnaire that measured students' perceptions through indicators of interest in participating in traditional sports learning, efforts to pay attention to learning, behavior during learning, facilities available during learning, and the role of lecturers in traditional games learning. The results indicated that students demonstrated a high level of interest in participating in traditional games learning, exhibited strong attention to the instructional materials, and showed positive behavioral engagement throughout the learning process. The availability of traditional sports facilities was perceived favorably, and the lecturer’s role in facilitating traditional games learning received strong positive evaluations from students. This indicates that students have a good perception of traditional sports and traditional sports are not only seen as enjoyable physical activities, but also as educational tools that have cultural value and are relevant to be preserved amidst the changing times.